2015
DOI: 10.1007/s10694-015-0551-5
|View full text |Cite
|
Sign up to set email alerts
|

Fire-Related Mortality in Sweden: Temporal Trends 1952 to 2013

Abstract: This study examines temporal trends in deaths due to fire-related accidents in Sweden from 1952 to 2013 based on statistics in the Cause of Death register held by the Swedish National Board of Health and Welfare. Fatalities coded with underlying cause of death associated with fire-related accidents are included and absolute numbers and age-adjusted mortality rates are calculated and statistically analysed for trends using Poisson regression. The results show a significant reduction in both absolute numbers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…First, children are not present in the sociodemographic data sources we used and therefore would have constrained us to approximate their status through their parents. Second, Sweden deviates from many other countries by having very few children dying in fire 3. Cases were identified from the national database on fatal fires and fire victims held by MSB.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, children are not present in the sociodemographic data sources we used and therefore would have constrained us to approximate their status through their parents. Second, Sweden deviates from many other countries by having very few children dying in fire 3. Cases were identified from the national database on fatal fires and fire victims held by MSB.…”
Section: Methodsmentioning
confidence: 99%
“…Mortality has decreased in many industrialised countries in recent decades 2. In absolute and relative terms, the situation in Sweden improved greatly from 1952 to 2013 3. However, compared with some similar countries, for example the UK, the USA, Norway and Canada, Sweden exhibits a relatively high fire mortality rate 2…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, although fire mortality has decreased from a general perspective, these reductions seem to have been disproportionate in terms of different socio-demographic groups, as well as there being a levelling-off of the decreasing trend. For example, whilst large decreases have been seen amongst adults and children, only minor rate reductions have been observed amongst older adults [4]. Also, in regards to older adults, several studies have suggested that the changing demographics, in which the number of older people are increasing substantially [5] will lead to increases in the number of deaths in countries such as Japan [6] and Spain [7].…”
Section: Introductionmentioning
confidence: 99%
“…The ageing process might worsen the ability of an individual to perform selfevacuation and demonstrate the importance of taking specific needs into consideration when functional capacity decreases and disability increases [69]. This is confirmed by the trends in fire-related deaths highlighting the vulnerability of older people, i.e., they have been shown to be at higher risk of dying in fire accidents [15,30]. For example, Boyce states that chronic conditions linked to ageing such as cardiovascular disease, stroke, diabetes, cancer, arthritis and osteoporosis, along with obesity, could prevent people from performing evacuation activities successfully [8].…”
Section: Introductionmentioning
confidence: 86%